Examining the joint effect of disability, health behaviors, and comorbidity on mortality in MS. Issue 5 (October 2016) - Salter, Amber; Tyry, Tuula; Wang, Guoqiao; Fox, Robert J.; Cutter, Gary; Marrie, Ruth Ann
Abstract: Background: In multiple sclerosis (MS), comorbidities have been associated with disability progression and an increased risk of mortality. We investigated the association between comorbidities and mortality in MS after accounting for disability and health behaviors. Methods: We followed North American Research Committee on Multiple Sclerosis (NARCOMS) Registry participants who completed the Fall 2006 survey on comorbidities until death (reported or matched in the National Death Index) or date of last follow-up in 2014. We used proportional hazards regression to investigate the association between comorbidities and mortality, controlling for demographic, clinical, health behavior, and disability factors. Results: Of 9, 496 participants meeting the inclusion criteria, 502 (5.3%) were deceased. Most participants reported having ⩽3 comorbid conditions (70.9% survivors, 76.9% decedents). In individual regression models, vascular, visual, and mental comorbidities were associated with increased mortality risk after adjustment for factors associated with survival. When combined into a single model, vascular (hazard ratio 1.269; 1.041–1.547), visual (1.490; 1.199–1.852), and mental comorbidities (excluding anxiety, 1.239; 1.024–1.499) remained independently associated with an increased risk of mortality. Conclusions: Presence of comorbidities was independently associated with an increased risk of mortality as compared to absence of comorbidities after adjusting for factors associated with survival. Specifically, vascular, visual, and mental comorbidities increased the risk of mortality. This highlights the need for clinicians to attend to these comorbidities, which can be modified by treatments or other interventions, and potentially reduce the risk of mortality in persons with MS who have these conditions.